The effect of place value board learning media on the learning outcomes of third-grade elementary school students - Adhwaul Mumtazah; Dya Ayu Agustiana Putri; Fera Dwidarti (Arshaka: Social Sciences and Education, 2026)
Mathematics learning in elementary schools still faces the problem of low student learning outcomes, especially in the material of place value of numbers, due to learning that tends to be abstract and minimal use of concrete learning media. This study aims to determine the effect of using the Place Value Board learning media on the mathematics learning outcomes of third-grade elementary school students. This study uses a quantitative approach with a quasi-experimental method through a nonequivalent control group design. The research subjects consisted of two classes, namely the experimental class given treatment using the Place Value Board media and the control class using conventional learning. Data were collected through learning outcome tests in the form of pretests and posttests that have been tested for validity and reliability. Data analysis was carried out using an independent sample t-test. The results showed that there was no significant difference between the two groups in the pretest, but there was a significant difference in the posttest with a significance value of p <0.001. This indicates that the use of the Place Value Board media has a significant effect in improving students' mathematics learning outcomes. Thus, the Place Value Board media is effective for helping students understand the concept of place value concretely. The implications of this study indicate that teachers are advised to utilize concrete learning media to improve the quality of mathematics learning in elementary schools.